Clinical Results of Utilizing the Satellite Rod Technique in Treating Ankylosing Spondylitis Kyphosis. Issue 9 (10th August 2022) - Liu, Chao; Hu, Fanqi; Hu, Wenhao; Zhang, Zhen; Zheng, Guoquan; Song, Kai; Li, Fangcai; Zhang, Xuesong
Abstract : Objective: According to the literature, there are no clinical reports documenting the use of the satellite rod technique in the treatment of ankylosing spondylitis kyphosis. The purpose of this retrospective study was to compare the clinical outcome of patients with ankylosing spondylitis kyphosis who adopted satellite rods versus those who did not. Methods: Patients with ankylosing spondylitis kyphosis who underwent one or two‐level pedicle subtraction osteotomy (PSO) were reviewed, and total of 119 patients (112 males and seven females, average age 39.89 ± 6.61 years) were eligible and included in this present study. Anterior–posterior and lateral full‐length spine X‐ray films were performed preoperatively and at the two‐year follow‐up visit. Global kyphosis (GK), lumbar lordosis (LL), thoracolumbar kyphosis (TLK), thoracic kyphosis (TK), and osteotomy angle (OA) were measured. The complications of every group of patients were collected. Pre‐ and postoperative health‐related quality of life instruments, including the Bath Ankylosing Spondylitis Functional Index (Basfi) and Scoliosis Research Society outcomes instrument‐22 (SRS‐22), were recorded. The patients were divided into three groups based on features of their osteotomy including PSO levels and whether the satellite rod technique was applied. Patients who underwent one‐level PSO without the satellite rod technique were categorized in the one‐level group. Patients who underwent one‐level PSO with the satellite rod technique were classified in the satellite rod group. Patients who underwent two‐level PSO without the satellite rod technique were included in the two‐level group. The paired sample t test was used to compare pre‐ and postoperative parameters. One‐way ANOVA was performed for multiple group comparisons. Results: The average follow‐up time is 29.31 ± 3.66 months. The patients' GK were significantly improved from 46.84 ± 20.37 degree to 3.31 ± 15.09 degree. OS achieved through each osteotomy segment of one‐level group (39.78 ± 12.29 degree) and satellite rods group (42.23 ± 9.82 degree), was larger than that of two‐level group (34.73 ± 7.54 and 28.85 ± 7.26 degree). There was no significant difference between the one‐level group and the satellite rod group in achieving the OS. Thirteen patients experienced different complications (10.92%). Three patients experienced rod fracture in the one‐level group. There was no rod fracture or screw failure in the satellite rod group or the two‐level group. Conclusion: The satellite rod technique is also recommended for patients who undergo PSO osteotomy to correct ankylosing spondylitis kyphosis deformities. Abstract : A 57 years old male patient, who experience the rod fracture 13 months after operation (as the figure A and figure B shows). The reoperation with satellite rod technique was performed for the patient (as the figure C and figure D shows).